Media sosial dan pengetahuan remaja tentang risiko pernikahan dini: kasus SMP Negeri 55 Barombong Makassar - Handayani, Sri; Bayuningrum, Pratiwi; Karnely, Karnely; Syaekhu, Ahmad; Paratama, Faradillah (GEOGRAPHIA : Jurnal Pendidikan dan Penelitian Geografi, 2025)
Early marriage remains a significant social issue in Indonesia, particularly among adolescents who have limited access to education and information. This study aims to analyze the role of social media as a source of information in shaping adolescents’ knowledge of the risks of early marriage. The study employs a quantitative approach with a cross-sectional design involving 70 junior high school students. Data were collected through a Likert-scale questionnaire and analyzed using descriptive analysis and the chi-square test. The results show that 70% of respondents had been exposed to information about early marriage through social media, and 62.9% had a relatively high level of knowledge. However, bivariate analysis indicates that there is no statistically significant relationship between the use of social media and adolescents’ level of knowledge (p = 0.914). These findings indicate that exposure to digital information does not automatically increase knowledge, as the process of understanding formation is influenced by social context and the educational environment. Social media functions as a supportive space for information diffusion within a broader social space system.